Chitosan-based lead ion-imprinted interpenetrating polymer network by simultaneous polymerization for selective extraction of lead(ii) - Hande, Pankaj E.; Kamble, Sanjay; Samui, Asit B.; Kulkarni, Prashant S. (Industrial & Engineering Chemistry Research, 2016)
In this study, we report the synthesis of a Pb(II) ion-imprinted interpenetrating polymer network (II-IPN) by simultaneous polymerization for selective extraction of Pb(II) from printed-circuit-board (PCB) recycling unit wastewater. Initially, a polymer network was synthesized by polymerization of methacrylic acid (monomer) and ethylene glycol dimethacrylate (cross-linker) and a second polymer network by chitosan (complexing monomer) and tetraethyl orthosilicate (cross-linker). The chemical structure and morphology of the II-IPN were analyzed using Fourier transform infrared, field-emission scanning electron microscopy, atomic force microscopy, and transmission electron microscopy. The interaction of the functionality in the II-IPN with Pb(II) through chelation was studied by X-ray photoelectron spectroscopy analysis. The maximum adsorption capacities for II-IPN and nonimprinted interpenetrating polymer network were 37.5 and 10.3 mg g(-1), respectively. The largest selectivity coefficient for Pb(II) in the presence of W(VI) was 161.58. The developed Pb(II) II-IPN was successfully employed for selective extraction of Pb(II) from PCB recycling unit wastewater.